Sankey diagrams for energy consumption and scope 2 carbon emissions in laser de-coating. (15th March 2022) - Ouyang, J.; Mativenga, P.; Liu, Z.; Goffin, N.; Jones, L.; Woolley, E.; Li, L.
Abstract: The Greenhouse Gas Protocol requires mandatory reporting of direct on-site emissions (Scope 1) and energy consumption derived emissions (Scope 2 emissions) for industry and business. This work modelled the energy requirements and associated emissions for laser selective removal of coatings from tooling to facilitate their use in a circular economy. Four different lasers with nanosecond and picosecond laser pulses were studied. System boundaries such as laser beam material interaction level, laser source level, and full laser system level were considered in understanding the electrical energy requirements and scope 2 carbon emissions. Generic energy operational states of a laser system were defined and used to evaluate energy requirements. The energy requirements are visualised through Sankey diagrams to aid effective communication of data and key areas for focus. A new metric of specific emissions is reported and provides normalised values for comparing laser processing to other competing cleaning technologies. The results show that developers of laser systems should focus on improving the laser source efficiency and design and development of energy efficient laser cooling systems. For manufacturers, in the transition to low carbon manufacturing, choice of laser systems and reducing the carbon intensity of the available electricity are key levers for significantly reducing emissions. The work contributes towards a deeper understanding of energy requirements and carbon emissions in laser material processing to inform the net zero transition. Highlights: A generic framework for evaluating the energy requirements of laser material processing. System boundaries at laser beam material interaction, laser source, and full laser system level. Sankey diagrams to communicate more effectively energy requirements. A new metric and data for specific scope 2 emissions for laser systems.